Retrospective study and review of polymorphous low‐grade adenocarcinoma - Pogodzinski, Matthew S. (2006)
Objectives/Hypothesis: We review a single institution's experience with polymorphous low‐grade adenocarcinoma. To our knowledge, this is the largest patient series of polymorphous low‐grade adenocarcinoma with clinical follow‐up in the otolaryngology literature. Study Design: We retrospectively identified 19 patients with polymorphous low‐grade adenocarcinoma who had adequate clinical follow‐up and pathologic specimens available for examination. Methods: All pathologic materials were reviewed by one head and neck pathologist. Results: The median follow‐up was 9.6 years. The most frequently affected sites were the hard palate (12 patients) and soft palate (9 patients). Fifteen patients had their initial treatment at our institution, and four patients presented with a recurrent tumor. Five patients had a local recurrence after surgery; of those patients, two had initially presented with recurrent tumors. Local tumors recurred as late as 15 years after the initial surgery. One patient had regional nodal disease 20 years after the initial procedure, and another had lung metastasis. No patients received chemotherapy. The most common initial diagnoses were polymorphous low‐grade adenocarcinoma, adenoid cystic carcinoma, and pleomorphic adenoma. Conclusions: Polymorphous low‐grade adenocarcinoma is an increasingly recognized malignancy that originates predominantly in the minor salivary gland. Our experience confirms good local control after a wide local excision is performed, but local recurrences can occur despite having negative margins after surgery. The delayed local recurrences and regional nodal metastases noted in our series show that prolonged follow‐up is needed. This series also reports one of the first pathologically confirmed cases of distant metastasis.